Do you prefer, Pinterest or Instagram? The role of image-sharing SNSs and self-monitoring in enhancing ad effectiveness. (May 2017) - Kim, Dong Hoo; Seely, Natalee Kate; Jung, Jong-Hyuok
Abstract: The current research applied self-monitoring theory to investigate how individuals' dispositional self-monitoring levels differ when exposed to two image-sharing social network sites (SNSs)—Pinterest and Instagram. Two consecutive studies were conducted. Through an online survey of 153 U.S. college students (study 1) the relationship between individuals' dispositional self-monitoring and their preference of image-sharing SNSs was investigated. And a lab experiment (study 2) involving a subset of the first sample (n = 61) was conducted to explore the impact of the image-sharing SNSs use on individuals' self-monitoring and determine advertisement message efficacy based on exposure to image-sharing social media. Results suggest that students in the low self-monitoring group interacted more intensely with Pinterest than Instagram. Additionally, individuals' interactions with Pinterest and Instagram influenced their dispostional self-monitoring levels, as well as their preferences toward different types of persuasive messages (image-oriented vs. product-oriented advertisement). Results indicate not only that self-monitoring can shift in the context of different image-based social media behaviors, but that self-monitoring as influenced by social media can have implications for advertising message efficacy. Highlights: Individuals' self-monitoring influence their image-sharing SNS use: Low self-monitors exhibited a higher intensity toward Pinterest than they did Instagram. Image-sharing SNS use can also influence individuals' self-monitoring: Using Pinterest decreased individuals self-monitoring whereas using Instagram increased their self-monitoring level. The relationship between self-monitoring and image-sharing SNSs use can influence how individuals evaluate different types of advertisements.